Analisis Efektivitas Teknik Tendangan Dollyo Chagi Melalui Metode Latihan Beban Kaki Terhadap Kecepatan Dan Akurasi Di Dojang TMC - Charmila Tandi Rerung (Program Studi Pendidikan Kepelatihan Olahraga, 2025)
This study aims to analyze the effectiveness of leg weight training methods on improving speed and accuracy of dollyo chagi kicks in TMC Taekwondo Mountain Child athletes. This research used a quasi-experimental design with pre-test and post-test control group design involving 20 taekwondo athletes divided into experimental group (n=10) and control group (n=10). The experimental group received leg weight training combined with conventional training for 8 weeks, while the control group only received conventional training. Speed was measured using photoelectric timing gates and accuracy using target scoring system. Data analysis used paired t-test and independent t-test with significance level α=0.05. Results showed significant improvement in experimental group for kick speed (12.3% improvement, p=0.003) and accuracy (15.7% improvement, p=0.002) compared to control group which only showed 2.5% and 4.2% improvement respectively. Comparison between groups showed significant differences (p<0.05) with experimental group being superior. Leg weight training method is effective for improving speed and accuracy of dollyo chagi kicks in TMC Mountain Child taekwondo athletes.